2023
DOI: 10.1088/2058-9565/accdfd
|View full text |Cite
|
Sign up to set email alerts
|

Emergent complex quantum networks in continuous-variables non-Gaussian states

Abstract: We use complex network theory to study a class of photonic continuous variable quantum states that present both multipartite entanglement and non-Gaussian statistics. We consider the intermediate scale of several dozens of modes at which such systems are already hard to characterize. In particular, the states are built from an initial imprinted cluster state created via Gaussian entangling operations according to a complex network structure. We then engender non-Gaussian statistics via multiple photon subtrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Although the study focused on ground states the relation was found to be robust to small temperatures. More recently, the impact of local operations on the structure of a correlation network has been considered [251]. The starting point was a Gaussian cluster state with an embedded network structure.…”
Section: Network Description Of Statesmentioning
confidence: 99%
“…Although the study focused on ground states the relation was found to be robust to small temperatures. More recently, the impact of local operations on the structure of a correlation network has been considered [251]. The starting point was a Gaussian cluster state with an embedded network structure.…”
Section: Network Description Of Statesmentioning
confidence: 99%